Proceedings of the International Conference on "Microwave and THz Technologies and Wireless communications". (IRPhE, 2018 September 19-21, Aghveran, Armenia)
The International Conference “Microwave & THz Technologies and Wireless Communications” (IRPhE’2018) was held in Aghveran, Armenia, from September 19 to September 21, 2018. The IRPhE’2018 Conference was an open forum for the presentation and discussion of advanced research achievements in Microwave and THz technologies, wireless communications, emerging electronic devices and materials.
Keywords: Physics; Electronic structure and electrical properties of surfaces; Instruments, apparatus, components common to several branches of physics; Electromagnetism; electron and ion optics; Optics; Materials science; Electronics; radiowave and microwave technology; direct energy conversion and storage; Electronic and magnetic devices; microelectronics